Design of polymorphic heterogeneous shell in relaxor antiferroelectrics for ultrahigh capacitive energy storage - Huifen Yu; Tengfei Hu; Haoyu Wang; He Qi; Jie Wu; Ruonan Zhang; Weisan Fang; Xiaoming Shi; Zhengqian Fu; Liang Chen; Jun Chen (Nature Communications)
Abstract Relaxor antiferroelectrics are considered promising candidate materials for achieving excellent energy storage capabilities. However, the trade-off between high recoverable energy density and high efficiency remains a major challenge in relaxor antiferroelectrics for practical applications. Herein, guided by phase-field simulation, we propose a strategy of designing polymorphic heterogeneous shell in core-shell dual-phase dielectrics to synergistically control micro and local heterostructures, resulting in comprehensive improvements in breakdown electric field, polarization fluctuation and saturation behaviors. Leveraging the core-shell effect and polarization heterogeneity, an ultrahigh recoverable energy density of 12.7 J cm-3 and an impressive efficiency of 87.2% are achieved in lead-free relaxor antiferroelectrics, making a performance breakthrough in core-shell dielectrics. This work opens up a new avenue to efficiently develop high-performance energy storage dielectrics and is expected to be popularized in other fields.